Analisis Persepsi Resiko Terhadap Minat Beli Produk Makanan Online Pada Aplikasi Shopee - Julianni, Herny; Rachmawati, Eva (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2024)
This research aims to determine risk perceptions regarding interest in purchasing food products online via Shopee. Using a qualitative approach with interviews, it evaluates the risks on e-commerce platforms, especially Shopee. The goal is to help the public understand potential risks to minimize losses for consumers. Uncertainty can lead to potential risks, often caused by a lack of information about future events, whether positive or negative. To address risks faced by Shopee consumers, structured interviews were conducted with 8 respondents. A prepared question guide was used to ensure consistency and comparability of data. The results show that product risk perceptions dominate consumer concerns when buying food online.